Directional dependent piezoelectric effect in CVD grown monolayer MoS2 for flexible piezoelectric nanogenerators. (April 2016) - Kim, Sung Kyun; Bhatia, Ravi; Kim, Tae-Ho; Seol, Daehee; Kim, Jung Ho; Kim, Hyun; Seung, Wanchul; Kim, Yunseok; Lee, Young Hee; Kim, Sang-Woo
Abstract: Due to the interesting semiconducting and optical properties of transition metal dichalcogenides, they have received particular attention for novel electronics and optoelectronics. In addition it is expected that piezoelectric properties of two-dimensional (2D) layered materials are very useful to realize next generation mechanically powered transparent flexible charge-generating devices. Here we report directional dependent piezoelectric effects in chemical vapor deposition grown monolayer MoS2 for flexible piezoelectric nanogenerators (NGs). It was found that the output power obtained from the NG with the armchair direction of MoS2 is about two times higher than that from the NG with the zigzag direction of MoS2 under the same strain of 0.48% and the strain velocity of 70 mm/s. This study provides a new way to effectively harvest mechanical energy using novel flexible piezoelectric NGs based on 2D semiconducting piezoelectric MoS2 for powering low power-consuming electronics and realizing self-powered sensors. Graphical abstract: We report directional dependent piezoelectric effects in chemical vapor deposition grown monolayer MoS2 for flexible piezoelectric nanogenerators. The output power obtained from the nanogenerator with the armchair direction of MoS2 is about two times higher than that from the nanogenerator with the zigzag direction of MoS2 under the same strain. Highlights: Directional dependent piezoelectric effects in chemical vapor deposition (CVD) grown monolayer MoS2 for flexible piezoelectric nanogenerators (NGs). Lateral piezoresponse force microscopy measurements revealed that the magnitude of the piezoelectric polarization in monolayer MoS2 significantly depends on the atomic orientation axis of MoS2 . Flexible piezoelectric NGs were successfully fabricated using the CVD-grown single-crystalline monolayer MoS2 flakes. The output power obtained from the NG with the armchair direction of MoS2 is about two times higher than the zigzag direction of MoS2 . New effectively harvest mechanical energy using novel flexible piezoelectric NGs based on 2D semiconducting piezoelectric MoS2 for powering low power-consuming devices and realizing self-powered electronics.